Through the Gates of Loving Inquiry: Discovering a Poetics of Relationship (LEARNing Landscapes, 2010)
I am a poet, arts-based researcher and healthy relationships educator. After many years of teaching about healthy relationships in the classroom, and writing poetry about my relationships with people, I moved to Butterstone Farm and discovered a new place of learning. Through the Gates of Loving Inquiry1 develops the conversation on how we may engage in loving relationships within and beyond the scope of our human relationships, expanding this pedagogical practice from the walls of schools and universities out toward our experience with nature.
Keywords: poetry; arts-based; healthy realtionship educator; experience; loving relationship